The Value of Serum CA125 in the Diagnosis of Borderline Tumors of the Ovary: A Subanalysis of the Prospective Multicenter ROBOT Study. Issue 7 (1st September 2015) - Fotopoulou, Christina; Sehouli, Jalid; Ewald-Riegler, Nina; de Gregorio, Nikolaus; Reuss, Alexander; Richter, Rolf; Mahner, Sven; Kommoss, Friedrich; Schmalfeldt, Barbara; Fehm, Tanja; Hanker, Lars; Wimberger, Pauline; et al.
Abstract : Objective: The value of the serum tumor marker CA125 in borderline tumors of the ovary (BOTs) is not well defined, with unclear benefit in both diagnosis and follow-up. The aim of the present project was to identify the predictive value of CA125 for stage and relapse. Methods: CA125 data were extracted from the ROBOT multicenter study of patients with BOT treated between 1998 and 2008 in 24 German centers. While patients' data were retrieved retrospectively from hospital records and clinical tumor registries, follow-up and independent central pathology review were performed prospectively. Results: We identified 127 patients from the ROBOT database fulfilling the eligibility criterion of available CA125 at initial diagnosis. Eighty-three (65.3%) patients had increased CA125 levels (>35 U/L). Of the patients, 85.0% presented with serous and 13.4% with mucinous BOT histology, whereas 29.9% had stage I disease. Fifteen (11.8%) patients experienced a relapse. Multivariate analysis identified raised CA125, young age, and serous histology as independent predictors of peritoneal implants of any type at initial presentation. Raised CA125 at initial diagnosis was, however, not an independent predictor of future relapse. Discussion: Elevated CA125 seems to be associated with the presence of peritoneal implants of any type at initial diagnosis of serous BOT, but failed to have any independent predictive value on future relapse. Prospective multicenter studies are warranted to evaluate CA125 measurements in the follow-up management of BOT.